Intergenerational Spillovers of Integration Policies: Evidence from Finland's Integration Plans - Pesola, Hanna; Sarvimäki, Matti (The Review of Economics and Statistics, 2024)
Abstract We examine the intergenerational effects of an integration program that increased language training and improved labor market outcomes of adult immigrants in Finland. Exploiting a discontinuity in the phase-in rule of a reform, we find that parents' participation in the program improved their children's grades by 0.5 standard deviations and extended their educational attainment by over a year. Two decades post-arrival, children of the affected immigrants earned 42% more than their counterparts whose parents narrowly missed the policy's implementation.